Health and wellness tourism. An opportunity for international specialization of La Palma - Aréstegui Ticona, Danitza Yulemy (2024)
This book, composed of six chapters, exposes the analysis of potential demand for health tourism and well being in La Palma (Spain). The plot narrative focuses on understanding preferences of potential tourists, identify opportunities development and position La Palma as a competitive destination in this type of tourism.